2017
DOI: 10.1038/nm.4343
|View full text |Cite
|
Sign up to set email alerts
|

Combined mutation in Vhl, Trp53 and Rb1 causes clear cell renal cell carcinoma in mice

Abstract: Clear cell renal cell carcinomas (ccRCC) frequently exhibit inactivation of the VHL tumour suppressor gene and often harbour multiple copy number alterations in genes that regulate cell cycle progression. We show here that modelling these genetic alterations by combined renal epithelium-specific deletion of Vhl, Trp53 and Rb1 in mice caused ccRCC. These tumours arose from proximal tubule epithelial cells and shared molecular markers and mRNA expression profiles with human ccRCC. Exome sequencing revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
129
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(146 citation statements)
references
References 56 publications
(81 reference statements)
10
129
0
Order By: Relevance
“…Exome sequencing from Harlander et al revealed that mouse and human clear cell renal cell carcinomas exhibited recurrent mutations in genes associated with the primary cilium, which strongly suggested the correlation between abnormality of ciliary genes and tumor 6. Seven DEGs including TUBB3 , AURKA , CENPF , STIL , STK39 , RAB23 and OSR1 were identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Exome sequencing from Harlander et al revealed that mouse and human clear cell renal cell carcinomas exhibited recurrent mutations in genes associated with the primary cilium, which strongly suggested the correlation between abnormality of ciliary genes and tumor 6. Seven DEGs including TUBB3 , AURKA , CENPF , STIL , STK39 , RAB23 and OSR1 were identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Reanalysis of the TCGA ccRCC data, focusing on cell cycle regulation, identified frequent copy number alterations of members of the p53 regulation and cell cycle checkpoint control clusters . Mutations in SWI–SNF members were not prevalent in this cohort, suggesting a different mechanism of oncogenesis.…”
Section: Cells Of Originmentioning
confidence: 81%
“…Though TP53 deletion or mutation is relatively uncommon in human ccRCC tumors, another study examined the effect of conditional Vhl , Trp53 , and Rb1 loss in the renal epithelium (utilizing Ksp -Cre), as changes in regulators of the p53 pathway and the G1/S cell cycle transition are frequently copy number modified according to The Cancer Genome Atlas (TCGA) data [49]. The authors found evidence of tumor onset as early as 7.5 months following triple knockout in a subset of mice, which were characterized by HIF-α and mTORC1 pathway activation by carbonic anhydrase 9 and phospho-4E-BP1 immunostaining, respectively.…”
Section: Genetic Mouse Models Of Renal Cell Carcinomamentioning
confidence: 99%